Effects of temperature and oxygen on 137Cs desorption from bottom sediment of a dam lake. (May 2022) - Tsuji, Hideki; Funaki, Hironori; Watanabe, Mirai; Hayashi, Seiji
Abstract: The temperature and oxygen environment play important roles in the desorption of 137 Cs from freshwater lake sediment to lake water. In this study, 12 quarterly surveys were performed to measure the dissolved 137 Cs concentration in surface and bottom lake water, the vertical distribution of water temperature, and the dissolved oxygen (DO) concentration at the upstream, midstream, and downstream sites of the Yokokawa Dam Lake in Fukushima Prefecture, Japan. Higher concentrations of dissolved 137 Cs were detected in the bottom water than in the surface water, especially in the summer and midstream lake regions at depths of 8–21 m owing to higher temperatures, which activated the bacterial decomposition of organic matter, and anaerobization, which enhanced the NH4 + in the pore water and 137 Cs desorption from mineral particles. To compare the effects of anaerobization and increasing temperature on 137 Cs desorption from sediment particles, intact sediment core samples were collected from the lake midstream and incubated for 1–14 days in a chamber under three controlled temperature and oxygen environment conditions: aerobic +10 °C; anaerobic +10 °C; and anaerobic +20 °C. The vertical distribution of 137 Cs in the sediment pore water showed a similar profile as NH4 + and K +, and both the increased temperature and reduced DO concentration enhanced the 137 Cs desorption. A comparison of the standard partial regression coefficients of temperature and DO concentration in the multiple regression equation for the 137 Cs concentration in pore water shows that the reduction of DO from saturation to zero at the water–sediment interface accelerated the desorption of 137 Cs more strongly than did the temperature rise from 10 to 20 °C. The experimental results show a nearly inverse proportional relationship between NH4 + and the distribution coefficients of 137 Cs after thermodynamic correction, except in the surface layer. These findings indicate that the 137 Cs concentration in pore water can be explained by the temperature-dependent chemical distribution between the solid–aqueous phase and its equilibrium with NH4 + . Graphical abstract: Image 1 Highlights: Dissolved 137 Cs in the midstream area of bottom lakewater is high in summer. Reduced dissolved oxygen promotes Cs desorption more than temperature rise. 137 Cs desorption in sediment appears to be determined by NH4 + dynamics.